Transformation of Ibn 'Arabi's Spiritual Values in Contemporary Life - Haqiqatullahil Kholidah; Fathiyaturrahmah Fathiyaturrahmah; Siti Raudhatul Jannah (The Eastasouth Journal of Social Science and Humanities, 2026)
The development of science and technology in the contemporary era has brought significant convenience to human life, yet it has also triggered a spiritual crisis marked by weakening moral values, growing materialism, and psychological anxiety. The dominance of rationalism distances individuals from the transcendental dimension, leading to a loss of life’s deeper meaning. This situation highlights the urgency of a spiritual approach capable of balancing intellectual advancement with inner fulfillment. This study explores the spiritual values in Al-Futūḥāt Al-Makkiyyah by Ibn ‘Arabi as a response to the spiritual challenges of modern society. The objectives are: (1) to analyze the concept of spiritual values in the work; (2) to examine the social settings influencing Ibn ‘Arabi’s thought; and (3) to investigate the transformation of these values in contemporary life. The research employs a qualitative approach using a character study through library research. Data are collected through symbolic and semantic reading and analyzed using Margrit Schreier’s theory. The findings reveal key spiritual concepts: Wahdat al-Wujud, Insan Kamil, and al-Hubb al-Ilahi. Influencing social factors include class, social roles, cultural norms, religiosity, and political-economic conditions. In modern life, these values transform into moral formation, spiritual awareness, meaningful living, and harmonious relationships between humans, nature, and God